The Nature of Bitcoin User Protection Against Transaction Fraud Online in Indonesia - Komang Sutriani; Johannes Ibrahim Kosasih; I Made Aditya Mantara Putra (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Rapid advances in information technology have fuelled the emergence of digital currencies such as Bitcoin as an increasingly popular means of transaction in Indonesia. However, behind the convenience and speed offered, the use of Bitcoin also poses a high risk of fraud in online transactions. The main objective of this research is to analyse the nature of legal protection for Bitcoin users in Indonesia. This research applies normative juridical method with statutory approach, conceptual approach, case study analysis, and refers to legal protection theory, online transaction theory, and legal economic theory. One of the case studies studied is the High Court Decision 1240/Pid.Sus/2022/PN Tng which reflects the existence of a vacuum and vagueness of legal norms in the protection of Bitcoin users. The analysis shows that although Bitcoin has been regulated under the legal framework of digital asset trading, there are still inefficiencies in the application of legal protection in a comprehensive and effective manner. This research emphasises the need for more progressive regulatory reforms, as well as strengthening the role of law enforcement agencies and financial technology supervisors to ensure fair, certain and comprehensive protection for Bitcoin users in the territory of Indonesia. It is hoped that the results of this research can strengthen theoretical contributions in enriching the development of digital economy law and become a practical reference for policy makers.